ANALISIS KEBIJAKAN PEMASARAN SEGMENTASI DEMOGRAFI NASABAH PENGAMBIL KREDIT PADA KOPERASI SIMPAN PINJAM KOPPONTREN ANNISA(Studi Kasus Koperasi Koppontren Annisa) - Susi Susanti; Muh. Sabir (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to determine the Demographic Segmentation Analysis of Credit Taking Customers at the Koppontren Annisa Savings and Loans Cooperative. To Group Customers. The research method used in this study is a descriptive method, namely a research method that describes a situation or event of a phenomenon. In this study, the data collection method used was documentation, interviews, questionnaires. The analysis used in this research is grouping analysis which is often known as cluster analysis. The results of this study indicate that customer demographic segmentation is divided into 3 clusters, namely cluster 1 based on age and income variables, cluster 2 based on gender variables and cluster 3 based on the last education variable